2015
DOI: 10.1007/s12035-015-9571-x
|View full text |Cite
|
Sign up to set email alerts
|

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder

Abstract: Post-traumatic stress disorder (PTSD) is a common psychiatric disease following exposure to a severe traumatic event or physiological stress, yet the precise mechanisms underlying PTSD remains largely to be determined. Using an animal model of PTSD induced by a single prolonged stress (SPS), we assessed the role of hippocampal nicotinamide adenosine dinucleotide phosphate (NADPH) oxidase 2 (NOX2) and parvalbumin (PV) interneurons in the development of PTSD symptoms. In the present study, behavioral tests were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 35 publications
4
36
1
Order By: Relevance
“…Furthermore, in both of these studies, treatment with medication resulted in a reduction in anxiety-like behaviours (as measured by the elevated plus maze test) to levels observed in non-stressed rats. Conversely, Liu et al (2016) did not find any difference in TNF-levels in the hippocampus of rats after SPS compared to nonstressed rats. No difference also observed in second assessment at one week after baseline.…”
Section: Study Findings: Animal Studiescontrasting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, in both of these studies, treatment with medication resulted in a reduction in anxiety-like behaviours (as measured by the elevated plus maze test) to levels observed in non-stressed rats. Conversely, Liu et al (2016) did not find any difference in TNF-levels in the hippocampus of rats after SPS compared to nonstressed rats. No difference also observed in second assessment at one week after baseline.…”
Section: Study Findings: Animal Studiescontrasting
confidence: 58%
“…Two of the studies measured TNF-levels (Levkovitz et al 2015, Liu et al 2016) and one assessed TNF-mRNA (Lee et al 2016) in the hippocampus of stressed rats. The results of these studies are presented in Table 1.…”
Section: Study Findings: Animal Studiesmentioning
confidence: 99%
“…Moreover, PV-positive GABAergic interneurons are closely linked to fear memory [27], which is also supported by our previous study [13].…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported that aversive foot shocks inhibit PV interneuron function, which reinforces postsynaptic foot shock responses and gates learning [12]. Consistently, our previous study has also demonstrated that phenotype loss of PV interneurons can elicit abnormal behaviors in a rat model of PTSD induced by single-prolonged stress [13]. These findings suggest that phenotype loss of PV interneurons and behavioral impairments associated with PTSD are casually linked.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation